EU Insights study on consumers and dietary sugars. Issue 3 (10th March 2022) - ,; Maxim, Laura; Mazzocchi, Mario; Van den Broucke, Stephan; Zollo, Fabiana; Rasche, Matthias; Ortega, Paul; Robinson, Tobin; Rogers, Claire; Vrbos, Domagoj; Zamariola, Giorgia; Smith, Anthony
Abstract: EFSA undertook consumer research on nutrition and dietary sugars awareness, knowledge and risk perception, preferred information sources and trust in different actors, plus additional research on stakeholder perspectives. The research results informed EFSA's communications and engagement for a public consultation on its draft scientific assessment of a Tolerable Upper Intake Level for dietary sugars, and upon its subsequent final publication. Interviews with the representatives of nine stakeholder organisations and two institutional partners were analysed for qualitative insights, which were used to validate and reinforce EFSA's outreach to partners and civil society organisations. A consumer survey was conducted among a representative sample of 7, 469 citizens (aged between 18 and 76) across EU Member States, Iceland and Norway in October and November 2020. The analysis of the quantitative data using segments derived from knowledge and risk perception indexes delivered important improvements for audience identification, messaging and choice of formats and channels for communication to the general public. The production of tips for risk communication on this topic used in combination with country‐specific data, provided both accessible and comprehensive support to risk communicators at the national competent authorities in EU Member States, Iceland and Norway.